Life-threatening bleeding with intussusception due to gastrointestinal stromal tumor: a case report - Kim, Min Sung (Surg Case Rep, 2019)
BACKGROUND: Massive intraluminal bleeding requires urgent intervention and management. However, the source of bleeding on the small intestine is difficult to determine. Intestinal tumor with intussusception is a rare and normally not an urgent condition. Herein, we present a rare case of intestinal intussusception with massive bleeding due to jejunal gastrointestinal stromal tumor (GIST) that required emergency surgical treatment. CASE PRESENTATION: A 51-year-old male was admitted to the emergency department complaining of abdominal pain and acute hematochezia. Esophagogastroduodenoscopy (EGD) and colonoscopy could not determine the source of the bleeding site. Abdominal pelvic computed tomography (AP-CT) revealed GIST with intussusception, strongly suggestive of distal jejunal bleeding. Unresponsive transfusion with low blood pressure and continuous hematochezia led to emergency laparotomy. GIST, which was the leading point for intussusception, was located in the jejunum and showed mucosal ulceration of approximately 3.5 cm in diameter. Following resection and functional anastomosis, histology revealed a GIST with low mitotic count (< 5 per 50HPF). Moreover, immunochemical analysis revealed positivity for c-kit (CD117) and DOG-1. There were no complications 2 months after surgery. CONCLUSIONS: Intussusception associated with GIST is a rare finding that can be life-threatening if it occurs with an ulcer. This case showed that the early detection of bleeding and emergency surgery could prevent severe complications.